2017
DOI: 10.1111/fare.12278
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Parental Disclosures to Children and Adolescents by Divorced and Married Parents

Abstract: Objective To examine individuals' attitudes about parental disclosures to children. Background Parents' disclosures can either help or hinder children's coping with family‐related stressors. Knowing what is appropriate to disclose, however, is not always clear. Method We examined judgments about parental disclosures using a mixed‐methods approach. In 18 factorial vignettes, information about a parent's marital status and gender and a child's age and gender were randomly varied; a convenience sample of 561 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We also were not able to examine or control for children's ages. It is likely that the information parents share with children is related to children's ages (e.g., Kang et al, 2017), and we were not able to explore that issue in this study. Also, participants were recruited from a divorced education course, which may limit the generalizability of the sample, although it should be noted that many courts in the United States require divorcing parents to attend parent education courses as part of their conditions.…”
Section: Limitationsmentioning
confidence: 95%
See 2 more Smart Citations
“…We also were not able to examine or control for children's ages. It is likely that the information parents share with children is related to children's ages (e.g., Kang et al, 2017), and we were not able to explore that issue in this study. Also, participants were recruited from a divorced education course, which may limit the generalizability of the sample, although it should be noted that many courts in the United States require divorcing parents to attend parent education courses as part of their conditions.…”
Section: Limitationsmentioning
confidence: 95%
“…Conversely, perceiving few benefits or greater risks may be related to later introductions of dating partners because parents want to be sure of the relationship before getting other family members involved. Public attitudes about what divorced parents should disclose to their children vary (Kang et al, 2017), although there is some consensus on what should not be shared (e.g., parental sexual behaviors) and what should be discussed (e.g., the parent-child bond). Disclosure about parents' dating relationships was a topic that most people in this convenience sample thought might be damaging to children (Kang et al, 2017).…”
Section: Introducing a New Dating Partner To Children And Coparentsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to CPM theory, parental disclosure and its effects are influenced by factors such as gender and marital status of parents and the child's age. for instance, mothers are more likely than fathers to disclose problems to their children (9). About the child's age, previous studies have found that the destructive effects of inappropriate parental disclosure on younger children are greater than on older children (13).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the phenomenon of disclosure and its effects among adults) 3), siblings (4), and friends (5) and also adolescents' disclosure to their parents (6) have been well studied, and its positive effects on people's relationships and health have been confirmed, but few studies have been conducted on parental disclosure to children (7). The topics that parents may disclose to their children include subjects related to their divorce (8), dating, disagreements over how to co-parent, daily activities, positive or negative comments about their spouse (7), their spouse's life (9), financial concerns (10), and spiritual disclosure) 11).…”
Section: Introductionmentioning
confidence: 99%